2021
DOI: 10.1371/journal.pone.0247181
|View full text |Cite
|
Sign up to set email alerts
|

Integration of transcriptomic and proteomic analyses for finger millet [Eleusine coracana (L.) Gaertn.] in response to drought stress

Abstract: Drought is one of the most significant abiotic stresses that affects the growth and productivity of crops worldwide. Finger millet [Eleusine coracana (L.) Gaertn.] is a C4 crop with high nutritional value and drought tolerance. However, the drought stress tolerance genetic mechanism of finger millet is largely unknown. In this study, transcriptomic (RNA-seq) and proteomic (iTRAQ) technologies were combined to investigate the finger millet samples treated with drought at different stages to determine drought re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Further, Chandra et al (2020) used transcriptomics to study Fe and Zn homeostasis of finger millet and identified 15 putative iron and zinc homeostasis pathway candidate genes. Li et al (2021) deployed transcriptomics and proteomics to determine drought response mechanisms and identified 113 associated differentially expressed genes (DEGs) and differentially expressed proteins (DEPs). Brhane, Haileselassie, Tesfaye, Ortiz, Hammenhag, Abreha, Vetukuri, and Geleta (2022) exploited transcriptomics for both marker and trait discovery.…”
Section: Genetic and Genomic Resources Of Finger Milletmentioning
confidence: 99%
“…Further, Chandra et al (2020) used transcriptomics to study Fe and Zn homeostasis of finger millet and identified 15 putative iron and zinc homeostasis pathway candidate genes. Li et al (2021) deployed transcriptomics and proteomics to determine drought response mechanisms and identified 113 associated differentially expressed genes (DEGs) and differentially expressed proteins (DEPs). Brhane, Haileselassie, Tesfaye, Ortiz, Hammenhag, Abreha, Vetukuri, and Geleta (2022) exploited transcriptomics for both marker and trait discovery.…”
Section: Genetic and Genomic Resources Of Finger Milletmentioning
confidence: 99%
“…Transcriptome profiling has been successful in identifying calcium sensor genes and their potential role in calcium transport (Mirza et al 2014;Sood et al 2016;Kokane et al 2018). Functional validation of genes involved in drought tolerance, including EcDehydrin7, EcGBF3, CIPK31, and TAF6, has been conducted using qRT-PCR Ramegowda et al 2017;Hittalmani et al 2017;Parvathi and Nataraja 2017;Parvathi et al 2019;Li et al 2021). RNA-sequencing is used to study the expression patterns for drought tolerance, high calcium content, and other important features (Kumar et al 2016a,b).…”
Section: Genomics-assisted Breedingmentioning
confidence: 99%
“…One of the significant drawbacks in this direction is the need for finger millet genomic resources. Transcriptome analysis of finger millet under salinity, drought stress, and developing spikes has been carried out in the past (Kumar et al 2015; Gururani et al 2020; Rahman et al 2014; Hittalmani et al 2017; Li et al 2021; Parvathi et al 2019).…”
Section: Introductionmentioning
confidence: 99%